Alzheimer’s disease: newer modalities in treatment - Syed, Ammaar Riyaz; Agha, Ayman Ahmad Alothman; Mohamed, Ibrahim Mirgani Saleem; Srinivasamurthy, Suresh Kumar (International Journal of Basic & Clinical Pharmacology, 2024)
Alzheimer’s disease (AD) remains insurmountable despite a long history of research and clinical development. It is projected to rise in the coming decades of public health due to the aging population worldwide. Understanding the basic tenets of the disease and targeting key steps remains a time-tested approach even for AD. Apart from the currently available treatment options namely NMDA blockers, and acetylcholinesterase inhibitors, recently monoclonal antibodies that target Aβ amyloid protein are approved. This review highlights the key features of currently approved drugs along with promising drugs in clinical development.